KAJIAN LITERATUR: PERAN ETIKA BISNIS TERHADAP KEPUASAN KONSUMEN - Queen Shakira Azzahra; Meesy Anugrah Putri; Salsabilla Ronardi; Alvi Nabilah; Agustiawan Agustiawan (Jurnal Ilmiah Akuntansi, 2025)
This study uses a literature review method with data sources taken from scientific journals to gain a deeper understanding of the role of business ethics in consumer satisfaction. This study aims to examine the role of business ethics on consumer satisfaction through a review of relevant literature. Business ethics include moral principles applied in company activities such as fairness, honesty, responsibility and transparency. The results of the study indicate that the implementation of good business ethics can increase consumer trust, loyalty and create a positive perception of the company. In addition, consistent implementation of business ethics has the potential to reduce conflict with consumers and improve the company's reputation in the market. Literature analysis indicates a positive relationship between business ethics and consumer satisfaction; consumers tend to feel more satisfied when companies demonstrate a commitment to ethical values ​​in their business practices. This study provides valuable insights for companies to strengthen sustainable business strategies based on ethical values, with the aim of improving consumer experience and competitiveness in the market.